LncRNA-MIAT-Mediated miR-214-3p Silencing Is Responsible for IL-17 Production and Cardiac Fibrosis in Diabetic Cardiomyopathy - Qi, Yanqing; Wu, Hongyu; Mai, Changjiang; Lin, Hanqun; Shen, Jia; Zhang, Xiaoyun; Gao, Yakun; Mao, Yong; Xie, Xupin (Frontiers in Cell and Developmental Biology, 2020)
Diabetic cardiomyopathy (DCM) represents an important complication of diabetes mellitus, with a silent development in its earlier stage and a deficient cardiomyocyte contractility in its late stage. So far, little advance has been achieved to reverse this pathological change. LncRNAs are a large cluster of RNAs that do not encode proteins, but have multiple functions in controlling gene expression. Interleukin-17 (IL-17), a proinflammatory cytokine, plays an important role in the pathogenesis of cardiac interstitial fibrosis. In this study, we reported that high glucose-induced lncRNA-MIAT upregulation is responsible for proinflammatory IL-17 production in cardiomyocytes. The underlying mechanism is likely due to that lncRNA-MIAT specific attenuates miR-214-3p-mediated inhibitory effect on IL-17 expression. As a result, attenuated IL-17 expression significantly ameliorate cardiac fibrosis, followed by improvement of cardiac contractility. In conclusion, our study first suggest that lncRNA-MIAT plays an important role in diabetic cardiomyopathy and targeting lncRNA-MIAT may become a potential strategy to treat DCM.